Sistem Informasi Posyandu Remaja Dalam Perkembangan Kesehatan Gizi dan Konseling Remaja Menggunakan Framework Codeigniter - Dewantari , Aneke; Prihantara, Andesita; Abdul Rohman Supriyono; Agung Hartono, Antonius (P3M Politeknik Negeri Cilacap, 2023)
Genius Youth Posyandu is the smallest health unit in the RW 14 area of ​​Sidanegara Subdistrict, Cilacap Regency which has the task of providing nutrition and health services to adolescents. So far, all series of Posyandu Adolescent activities are recorded conventionally in a book. The emergence of time inefficiency due to the limited number of cadres and the large number of young members of the Youth Posyandu. The difficulty of monitoring the development of nutritional health and nutrition counseling that has been carried out has also become a concern of cadres in the process of reporting Posyandu Adolescent activities to the Kelurahan level. system using blackbox testing. After testing this system, it was proven that all system functions were running well so that it made it easier for cadres to manage adolescent Posyandu anthropometric data, cadres to identify adolescent nutrition trends, and youth to view Posyandu data and offer counseling online.